Using Virtual Reality as Support to the Learning Process of Forensic Scenarios - Walid M. Khalilia; Miroslav Gombar; Zuzana Palkova; Michal Palko; Jan Valicek; Marta Harnicarova (IEEE Access, 2022)
Virtual Reality (VR) represents a computer technology to create a simulated three-dimensional (3D) environment. Compared to the traditional user interfaces, VR places the user inside an experience. This research aimed to implement and examine modern learning strategies and activities with the VR for teaching crime scene investigation. The target group of this piloting study consisted of all students who enrolled in a crime scene investigation course at Al-Istiqlal University during the Spring semester of 2021. An online item-based questionnaire has been developed. It is used to assess students’ perceptions towards using cooperative, discussion, field trip and problem-solving learning strategies and activities implemented with the VR technology. This study showed that VR is a helpful tool to practice modern learning strategies and skills in learning forensic science and crime scene investigation. We can conclude that using VR technology for educational purposes supports the learning process.